A Cross Cultural Understanding of English-Speaking Cultures: British, American, Australian, and Canadian Perspectives - Nur Indah Ramadhani Nasution; Suadi (Yayasan Al-Afif, 2026)
The findings reveal that each culture possesses its unique communication techniques, shaped by its social and historical context. American culture values directness, originality, and efficiency in communication, whereas British culture prioritises politeness and indirectness. Canadian culture is a mixture of civility and multicultural awareness, but Australian culture is characterised by informality, humour and equality. Such differences have a real impact on how people use English in everyday life, including how they communicate their ideas, make requests, and relate to others. Ignoring cultural context when using language might lead to misunderstandings. Therefore, attaining effective communication requires cultural awareness. This study emphasises how crucial it is to incorporate cultural awareness into English language instruction to foster intercultural competency. In conclusion, English is not culturally neutral, and being aware of cultural differences can enhance communication in international settings.